PENGARUH CURRENT RATIO, TOTAL ASSET TURNOVER, NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PADA PT HM SAMPOERNA Tbk BEI - Afriyeni, Afriyeni; Waldelmi, Idel; Pahlawan, Ryan (Komunitas Manajemen Kompetitif, 2023)
This study aims to determine whether there is an effect of Current Ratio (CR), Total Asset Turnover (TATO), and Net Profit Margin (NPM) on profit growth at PT HM Sampoerna Tbk on the Indonesia Stock Exchange in 2017-2021. This type of research is quantitative, while the data used is secondary data obtained from the financial statements of PT HM Sampoerna Tbk for 2017-2021. Data analysis techniques used descriptive statistical tests, normality tests, classic assumption tests, multiple linear regression analysis, hypothesis testing which consisted of partial tests (t test) and simultaneous tests (f test) and R2 determinant coefficient tests were processed using SPSS version 25. The results of this study indicate that the results of the t current ratio (CR) test and total asset turnover (TATO) partially (t test) have no effect on profit growth, and net profit margin (NPM) partially affect profit growth. Meanwhile, simultaneously (f test) shows that the current ratio (CR), total asset turnover (TATO), and net profit margin (NPM) have an effect on profit growth.